2009
DOI: 10.1021/jp903557m
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Geometrical Analysis of Dense Clusters with Variable Fractal Dimension

Abstract: The generation and geometrical analysis of clusters composed of rigid monodisperse primary particles with variable fractal dimension, df, in the range from 2.2 to 3 are presented. For all generated aggregate populations, it was found that the dimensionless aggregate mass, i, and the aggregate size, characterized by the radius of gyration, Rg, normalized by the primary particle radius, Rp, follow a fractal scaling, i = kf(Rg/Rp)df. Furthermore, the obtained prefactor of the fractal scaling, kf, is related to df… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 63 publications
9
86
0
Order By: Relevance
“…hR g i d f (1Àc) , with a value equal to 1.33 was obtained, which is in good agreement with the literature data. 77,84 By combining all this information, we can conclude that for the investigated colloidal system (surfactantfree polystyrene latex with relatively large surface charge density) aggregated under turbulent conditions, the structure and shape of aggregates are independent of the type of device, and further the CMD is indeed affected by the heterogeneity of the flow field, but identical scaling behavior of hR g i and I(0) n with the hydrodynamic stress for all devices has been obtained. This is in agreement with the conception of aggregate breakup occurring in the viscous subrange, where the characteristic length scale, g K , scales independently from device geometry with ffiffiffiffiffiffiffiffi ffi v 3 =e 4 p .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…hR g i d f (1Àc) , with a value equal to 1.33 was obtained, which is in good agreement with the literature data. 77,84 By combining all this information, we can conclude that for the investigated colloidal system (surfactantfree polystyrene latex with relatively large surface charge density) aggregated under turbulent conditions, the structure and shape of aggregates are independent of the type of device, and further the CMD is indeed affected by the heterogeneity of the flow field, but identical scaling behavior of hR g i and I(0) n with the hydrodynamic stress for all devices has been obtained. This is in agreement with the conception of aggregate breakup occurring in the viscous subrange, where the characteristic length scale, g K , scales independently from device geometry with ffiffiffiffiffiffiffiffi ffi v 3 =e 4 p .…”
Section: Discussionmentioning
confidence: 65%
“…Subsequently, the perimeter fractal dimension can be used to evaluate the mass fractal dimension using correlations as presented by Lee and Kramer 83 or by Ehrl et al 84 As it was shown by Ehrl et al, 84 this is a very robust method to evaluate the structure of compact aggregates. Detailed description of the experimental methodology, the used measurement techniques, and measurement data analysis can be found in our previous work.…”
Section: Stirring Devices and Fluid Flow Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter issue holds only for 2D pictures, as CM allows resolving a complete 3-D picture of the cluster [14]. However, even in the case of dense clusters, with a fractal dimension higher than 2, from the projection, it is possible to estimate a perimeter fractal dimension, which can be related to the real fractal dimension through known correlations [21,22].…”
Section: Microscopy Techniquesmentioning
confidence: 99%
“…In fact all aggregates can be characterized by the same perimeter fractal dimension d pf 18,64,65 which in this particular case was equal to 1:14 (see Figure 2). Having determined d pf the mass fractal dimension d f was subsequently estimated using a correlation developed by Ehrl et al, 66 which for this particular case was equal to 2.7, indicating very compact aggregates. Similarly to the d f also the aspect ratio of formed aggregates did not change (see Figure 3), which is indicating that populations of formed fragments are rather similar independent whether breakup occurs under turbulent or laminar conditions.…”
mentioning
confidence: 99%